Increasing Financial Inclusion towards Reducing Poverty Levels in Indonesia: A Literature Review - Digdowiseiso , Kumba; Setiawan, Heru Dian (CV ODIS, 2023)
Financial inclusion has risen to the top of the global reform agenda, owing to its ability to break the cycle of poverty and reduce income disparities. The purpose of this study is to look into promoting financial inclusion in order to reduce poverty levels in Indonesia. A literature study from national and international journal sources was employed in this research, with a time frame of 2019-2023. The research findings indicate that financial inclusion is critical since it refers to the general public's and businesses' access to and utilization of acceptable financial services. Financial inclusion can promote economic growth while enhancing the economy for society. In addition, financial inclusion is a strategy that the government can use with private support to overcome poverty through the National Strategy Program for Financial Inclusion and Improvement of Banking Infrastructure.